Playing to our human strengths to prepare medical students for the future - Chen, Julie (Korean J Med Educ, 2017)
We are living in an age where artificial intelligence and astounding technological advances are bringing truly remarkable change to healthcare. Medical knowledge and skills which form the core responsibility of doctors such as making diagnoses may increasingly be delivered by robots. Machines are gradually acquiring human abilities such as deep learning and empathy. What, then is the role of doctors in future healthcare? And what direction should medical schools be taking to prepare their graduates? This article will give an overview of the evolving technological landscape of healthcare and examine the issues undergraduate medical education may have to address. The experience at The University of Hong Kong will serve as a case study featuring several curricular innovations that aim to empower medical graduates with the capabilities to thrive in the future.